Komposisi Botani, Persentase dan Kualitas Tanaman Pakan Sapi di Kabupaten Sumbawa Barat - Dahlanuddin Dahlanuddin; Mardiansyah Mardiansyah; Sukarne Sukarne; Oscar Yanuarianto; Andika Saputra; Yusuf Akhyar Sutaryono Sutaryono (Postgraduate, University of Mataram, 2023)
This study aims to determine the botanical composition, percentage, and quality of plant feed given to cattle. The research was carried out in West Sumbawa Regency, using a survey method or direct observation in the field with a purposive sampling technique of 50 cattle breeders in Sumbawa Regency. The method used is by weighing the fresh weight of the whole feed given to the cows. Forage plants were observed by separating the plants based on their type, then identified each type of forage plant that has been separated using the help of the Plant Net application and followed by proximate analysis. The results showed that the botanical composition consisted of 19 types of forage plants, namely 6 types of legumes, 4 types of grasses, 2 types of agricultural waste, and 7 types of weeds. The percentage of forage feed respectively is legumes (53%), grass (43%), agricultural waste (3%), and others (1%). Leguminous feed was dominated by lamtoro (46.16%) and other legumes (6.37%). The quality of feed given to cattle is of good quality due to the dominance of forage legumes in feed with a crude protein content of 16.06%.